Effects of endogenous and exogenous oestrogen exposure on hearing level in postmenopausal women: A cross‐sectional study. (15th January 2021) - Suh, Michelle J.; Oh, Sun Kyung; Lee, Soo Bin; Kim, Sung Huhn
Abstract: Objective: To investigate the effect of endogenous and exogenous oestrogen exposure on hearing levels in postmenopausal women. Study Design: Retrospective cross‐sectional study. Setting: Population‐based survey data collected by the Korean National Health and Nutrition Survey between 1 January 2010 and 31 December 2012. Subjects and Methods: Participants comprised 3653 postmenopausal women. Detailed histories for reproductive factors and data on the use of hormone replacement therapy were obtained through health questionnaires and otologic examinations, including pure‐tone audiogram and otoscopic findings. Complex‐sample linear regression models controlling for confounding factors were generated to determine whether hormone‐related factors were associated with hearing loss. Results: Women who experienced a longer duration of oestrogen exposure had better hearing compared to those who do not in multivariate model adjusting for confounding factors with a lower adjusted beta coefficient of hearing threshold (β = −0.18, 95% confidence interval = −0.3 to −0.07, P  = .002). The results also suggested that hormone replacement therapy may be beneficial for attenuating hearing loss (β = −1.22, 95% confidence interval = −2.19 to −0.25, P  = .014), particularly in the high‐frequency range from 3 to 6 KHz. Conclusion: A longer duration of lifetime oestrogen exposure (LEE) and the use of hormone replacement therapy are likely to attenuate hearing loss. These epidemiologic data provide evidence that oestrogen may be beneficial for attenuating age‐related hearing decline.